Complete genome sequence of chloroplast DNA (cpDNA) of Chlorella sorokiniana. (3rd March 2016) - Orsini, Massimiliano; Cusano, Roberto; Costelli, Cristina; Malavasi, Veronica; Concas, Alessandro; Angius, Andrea; Cao, Giacomo
Abstract: The complete chloroplast genome sequence of Chlorella sorokiniana strain (SAG 111–8 k) is presented in this study. The genome consists of circular chromosomes of 109, 811 bp, which encode a total of 109 genes, including 74 proteins, 3 rRNAs and 31 tRNAs. Moreover, introns are not detected and all genes are present in single copy. The overall AT contents of the C. sorokiniana cpDNA is 65.9%, the coding sequence is 59.1% and a large inverted repeat (IR) is not observed.